2008
DOI: 10.1002/jctb.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner water using bimetallic nanoparticle catalysts

Abstract: Groundwater contaminated by hazardous chlorinated compounds, especially chlorinated ethenes, continues to be a significant environmental problem in industrialized nations. The conventional treatment methods of activated carbon adsorption and air-stripping successfully remove these compounds by way of transferring them from the water phase into the solid or gas phase. Catalysis is a promising approach to remove chlorinated compounds completely from the environment, by converting them into safer, non-chlorinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 43 publications
2
95
0
2
Order By: Relevance
“…It is interesting to tune the catalytic performance by using supported alloy catalysts [228][229][230][231][232][233][234]. For instance, Crooks and co-workers synthesized PdAu/TiO 2 using dendrimer-encapsulated alloy nanoparticles as the precursor, and found that the activities of the catalysts in CO oxidation followed the sequence PdAu/TiO 2 > Pd/TiO 2 > Au/TiO 2 [235].…”
Section: In Situ Transformation Of Niau/sio2 Into Au-niomentioning
confidence: 99%
“…It is interesting to tune the catalytic performance by using supported alloy catalysts [228][229][230][231][232][233][234]. For instance, Crooks and co-workers synthesized PdAu/TiO 2 using dendrimer-encapsulated alloy nanoparticles as the precursor, and found that the activities of the catalysts in CO oxidation followed the sequence PdAu/TiO 2 > Pd/TiO 2 > Au/TiO 2 [235].…”
Section: In Situ Transformation Of Niau/sio2 Into Au-niomentioning
confidence: 99%
“…Supported gold nanoparticles (GNPs) have been widely used in many catalytic reactions, e.g., hydrogen purification for fuel cells [1,2], synthesis of fine chemicals [3,4], control of environmental pollution [5], electrocatalysis [6,7], and many other organic reactions [8][9][10][11][12]. There are many recent reviews on different applications of gold catalysts, e.g., in selective oxidation [13][14][15][16] and hydrogenation reactions [3,17] to show their industrial prospects [18].…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] These NPs exhibit a clear catalytic activity volcano dependence on Pd surface coverage (or equivalently, Pd content) for trichloroethene and perchloroethene HDC reactions. 52,53 Recent calculations indicate that the Pd-on-Au catalysts are less expensive than Pd-only catalysts, 54 and that the metal catalysis approach is no more expensive than granulated activated carbon adsorption, air-stripping, or permeable reactive barrier technologies. 55 In this work, we explored Pd/Al 2 O 3 and Pd/Au/Al 2 O 3 of several compositions for room-temperature CF HDC in water.…”
mentioning
confidence: 99%